0
$\begingroup$

Let $f$ be irreducible and separable over $k$ and $\text{char}(k) \neq 2, 3$. Further let $f(x) = x^4 +px^2 +qx + r = (x-\alpha_1)(x-\alpha_2)(x-\alpha_3)(x-\alpha_4)$ which splits over $K$.

Then:

$G:=\text{Gal}(f)\hookrightarrow S_4$

$G\cap V_4$ is a normal subgroup of $G$, with $V_4 = \{\text{id},(12)(34),(13)(24),(14)(23)\}$

Now, the situation is as follows:

$k$ --- $K^{G\cap V_4}$ --- $K$

Letting $\beta := \alpha_1 + \alpha_2, \;\gamma := \alpha_1 + \alpha_3, \;\delta := \alpha_1 + \alpha_4$ we get (considering that $\alpha_1 + \alpha_2 +\alpha_3 + \alpha_4 = 0$):

$\beta^2 = (\alpha_1 + \alpha_2)^2 = -(\alpha_1 + \alpha_2)(\alpha_3 + \alpha_4)$

$\gamma^2 = (\alpha_1 + \alpha_3)^2 = -(\alpha_1 + \alpha_3)(\alpha_2 + \alpha_4)$

$\delta^2 = (\alpha_1 + \alpha_4)^2 = -(\alpha_1 + \alpha_4)(\alpha_2 + \alpha_3)$

$\Rightarrow \sigma(\beta^2)=\beta^2, \sigma(\gamma^2)=\gamma^2, \sigma(\delta^2)=\delta^2\;\; \forall \sigma \in G\cap V_4$

$\Rightarrow k(\beta^2, \gamma^2, \delta^2)\subseteq K^{G\cap V_4}$

Now,

$\alpha_1 = \frac{1}{2}(\beta + \gamma + \delta)$

$\alpha_2 = \frac{1}{2}(\beta - \gamma - \delta)$

$\alpha_3 = \frac{1}{2}(-\beta + \gamma - \delta)$

$\alpha_4 = \frac{1}{2}(-\beta - \gamma + \delta)$

$\Rightarrow k(\beta^2, \gamma^2, \delta^2)(\beta, \gamma, \delta) = k(\beta, \gamma, \delta) = k(\alpha_1, \alpha_2, \alpha_3) = K$

Here comes the part I don't understand:

$\Rightarrow \sigma \in \text{Gal}(K/k(\beta^2, \gamma^2, \delta^2)) \Rightarrow \sigma^2 = \text{id}$

Why does $\sigma \in \text{Gal}(K/k(\beta^2, \gamma^2, \delta^2))$ imply $\sigma^2 = \text{id}$?

$\endgroup$
1
$\begingroup$

If $\sigma \in Gal(K/k(\beta^2,\gamma^2,\delta^2))$, then by definition $\sigma(\beta^2)=\beta^2$, $\sigma(\gamma^2)=\gamma^2$, and $\sigma(\delta^2)=\delta^2$, because $\sigma$ fixes $k(\beta^2,\gamma^2,\delta^2)$. Now look at the expressions you listed for $\beta^2$, $\gamma^2$, and $\delta^2$, $$\beta^2=-(\alpha_1 + \alpha_2)(\alpha_3 + \alpha_4)$$ $$\gamma^2=-(\alpha_1 + \alpha_3)(\alpha_2 + \alpha_4)$$ $$\delta^2=-(\alpha_1 + \alpha_4)(\alpha_2 + \alpha_3)$$

and consider the effect of any permutation $\sigma'$ not in $V_4$. In particular, observe that two of the equalities $\sigma'(\beta^2)=\beta^2$, $\sigma'(\gamma^2)=\gamma^2$, $\sigma'(\delta^2)=\delta^2$ fail to hold. This implies that $Gal(K/k(\beta^2,\gamma^2,\delta^2)) = G\cap V_4$ and $\sigma^2=$ id. Hope this helps!

$\endgroup$
  • $\begingroup$ Yes, that helps. Thank you very much! :) $\endgroup$ – Miriam Feb 17 '16 at 6:51

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.